A Political Philosophy in Public Life : Civic Republicanism in Zapatero's Spain - Martí, Jose Luis, 1975-; Pettit, Philip, 1945- (Book collections on Project MUSE., 2010)
This book examines an unlikely development in modern political philosophy: the adoption by a major national government of the ideas of a living political theorist. When Jose Luis Rodríguez Zapatero became Spain's opposition leader in 2000, he pledged that if his socialist party won power he would govern Spain in accordance with the principles laid out in Philip Pettit's 1997 book Republicanism, which presented, as an alternative to liberalism and communitarianism, a theory of freedom and government based on the idea of nondomination.